Ceramic inlays: Effect of mechanical cycling and ceramic type on restoration-dentin bond strength - Trindade, F. Z. [UNESP]; Kleverlaan, C. J.; Da Silva, L. H.; Feilzer, A. J.; Cesar, P. F.; Bottino, M. A. [UNESP]; Valandro, L. F. (Operative Dentistry, 2016)
This study aimed to evaluate the bond strength between dentin and five different ceramic inlays in permanent maxillary premolars, with and without mechanical cycling. One hundred permanent maxillary premolars were prepared and divided into 10 groups (n=10) according to the ceramic system (IPS e.Max Press; IPS e.Max CAD; Vita PM9; Vita Mark II; and Vita VM7) and the mechanical cycling factor (with and without [100 N, 2 Hz, 1.2×106cycles]). The inlays were adhesively cemented, and all of the specimens were cut into microbars (1x1 mm, nontrimming method), which were tested under microtensile loading. The failure mode was classified and contact angle, roughness, and microtopographic analyses were performed on each ceramic surface. The mechanical cycling had a significant effect (p=0.0087) on the bond strength between dentin and IPS e.max Press. The Vita Mark II group had the highest bond strength values under both conditions, with mechanical cycling (9.7±1.8 MPa) and without (8.2±1.9 MPa), while IPS e.Max CAD had the lowest values (2.6±1.6 and 2.2±1.4, respectively). The adhesive failure mode at the ceramic/cement interface was the most frequent. Vita Mark II showed the highest value of average roughness. IPS e.max Press and Vita Mark II ceramics presented the lowest contact angles. In conclusion, the composition and manufacturing process of ceramics seem to have an influence on the ceramic surface and resin cement bond strength. Mechanical cycling did not cause significant degradation on the dentin and ceramic bond strength under the configuration used.